High prevalence and co-occurrence of modifiable risk factors for non-communicable diseases among university students: a cross-sectional study - Cicekli, Ipek; Gokce Eskin, Serap (Frontiers in Public Health, 2025)
BackgroundNon-communicable diseases (NCDs) are a major global concern. This study aimed to examine the prevalence and co-occurrence of lifestyle risk factors among university students.MethodsThis analytical, cross-sectional study was conducted between January and April 2022. A total of 485 students were included in the study. Lifestyle risk variables for NCDs included physical inactivity, low fruit and vegetable consumption, alcohol use, tobacco smoking, being overweight/obese, and sugar sweetened beverages consumption.ResultsOur results showed that the most frequent risk factor was insufficient physical activity (89.2%), followed by low vegetable (70.5%) and fruit consumption (58.9%). Overall, more than half of the students (51.2%) had four or more risk factors highlighting the urgent need for preventive interventions. The co-occurrence of four or more lifestyle risk factors was significantly greater in students at private universities (aOR: 2.01 95% CI: 1.2; 3.35), those living in student homes (aOR: 3.57 95% CI: 1.96; 6.5), and those with fast food preferences when eating outside (a0R: 2.53 95% CI: 1.62; 3.96).ConclusionTargeted university-based interventions, such as promoting physical activity, providing affordable nutritious meals, and educating students on healthy lifestyles, are essential to reduce non-communicable disease (NCD) risk among students. Early action fosters lifelong healthy habits, supports healthy aging, and reduces healthcare costs. Future research should focus on refining these strategies to maximize their impact on university populations.